Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

y = 5х – 7
—3х – 2 y = -12


Sagot :

[tex]-3x-2(5x-7)=-12\\-3x-10x+14=-12\\-13x=-26\\x=2\\\\y=5(2)-7\\y=10-7\\y=3[/tex]

Answer:

[tex](x, y) = (-\frac{29}{2}, -12)[/tex]

Step-by-step explanation:

[tex]-12 = 5 x ( -\frac{29}{2} ) - 7 - 3 x ( -\frac{29}{2} ) - 2 x (-12) = -12[/tex]